Impact of Collaborative Instructional Leadership of Principals and Teachers on Students’ Academic Performance in Secondary Schools in North Central Nigeria - ISAH, JOSEPH; Dr Agbe; Joseph Ityokyaa (IJRDO- Journal of Educational Research, 2019)
Abstract - This study investigated the ‘Impact of Collaborative Instructional Leadership of Principals and Teachers on Students’ Academic Performance in Secondary Schools in North Central Nigeria’. It was guided by three specific objectives and three research questions. Three hypotheses were formulated and tested at 0.05 level of significance. The study adopted a survey research design and the study area was North Central Nigeria. The population of the study was 16671, comprising 972 principals and 15699 teachers from 972 public secondary schools in the states North Central Nigeria. The sample size for the study was 391 subjects, consisting of 36 principals and 355 teachers and it was drawn using Taro Yamen formula for sample size determination. The instrument used for data collection was structured questionnaire titled, “Impact of Collaborative Instructional Leadership on Students’ Academic Performance Questionnaire (ICILSAPQ)” constructed by the researchers. The study used Mean and Standard Deviation to answer the research questions while Chi-square statistic was used to test the hypotheses at 0.05 level of significance. The mean of 2.50 and above was used to arrive at the decision level for the research questions. The study found that jointly providing incentives for teachers, providing incentives for learning, promoting professional development for teachers had impact on students’ academic performance in secondary schools in North Central Nigeria. The study recommended that Ministries of Education in the states of North Central Nigeria are to ensure that incentives are given to teachers who are adjudged to have performed above others; that principals liaise with the Ministries of Education of affected states to ensure that adequate instructional materials, varieties of teaching methods, relevant textbooks, among others, are provided; and that both Federal and State Governments as employers through principals should provide training and re-training opportunities for teachers to improve in knowledge and methodology to enhance and sustain students’ academic performance in secondary schools in North Central Nigeria.